2014
DOI: 10.1007/978-3-319-08786-3_3
|View full text |Cite
|
Sign up to set email alerts
|

The Magic Barrier of Recommender Systems – No Magic, Just Ratings

Abstract: Abstract. Recommender Systems need to deal with different types of users who represent their preferences in various ways. This difference in user behaviour has a deep impact on the final performance of the recommender system, where some users may receive either better or worse recommendations depending, mostly, on the quantity and the quality of the information the system knows about the user. Specifically, the inconsistencies of the user impose a lower bound on the error the system may achieve when predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…These conclusions are consistent with those reported in (Bellogín et al, 2014), that showed that with a neighbor-based approach, exploiting only inconsistent users to compute recommendations for inconsistent users does not lead to accurate recommendations.…”
Section: The Gsuonly Modelsupporting
confidence: 82%
See 3 more Smart Citations
“…These conclusions are consistent with those reported in (Bellogín et al, 2014), that showed that with a neighbor-based approach, exploiting only inconsistent users to compute recommendations for inconsistent users does not lead to accurate recommendations.…”
Section: The Gsuonly Modelsupporting
confidence: 82%
“…This is also the conclusion reported in (Bellogín et al, 2014): "less coherent users need information from outside of their own cluster".…”
Section: The Gsuonly Modelsupporting
confidence: 68%
See 2 more Smart Citations
“…Several approaches have been introduced to handle the natural noise in recommender systems [3,5,11,13]. O'Mahony et al [13] classified noise in recommender systems into natural (naturally occurred) and malicious (deliberately inserted) and proposed to remove noisy ratings to improve accuracy.…”
Section: Introductionmentioning
confidence: 99%